2020
DOI: 10.3389/fpls.2020.587264
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Contrasting Genotypes/Cultivars for Developing Heat Tolerance in Agricultural Crops: Current Status and Prospects

Abstract: Heat Tolerance in Crops contrasting genotypes and would pave the way for characterizing the underlying molecular mechanisms, which could be valuable for engineering plants with enhanced thermotolerance. Wherever possible, we discussed breeding and biotechnological approaches for using these traits to develop heat-tolerant genotypes of various food crops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 396 publications
4
42
0
2
Order By: Relevance
“…Heat stress caused MDA contents to decrease significantly in D-09013 and CH104/06, so these genotypes could have better adaptation capacity under heat stress. These results were in accordance with a previous report, in which heat tolerant chickpea genotypes had a lower accumulation of MDA as compared to sensitive genotypes (Chaudhary et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Heat stress caused MDA contents to decrease significantly in D-09013 and CH104/06, so these genotypes could have better adaptation capacity under heat stress. These results were in accordance with a previous report, in which heat tolerant chickpea genotypes had a lower accumulation of MDA as compared to sensitive genotypes (Chaudhary et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…In general, heat stress reduced plant growth, specially shoot or root length and shoot or root dry weight in chickpea, heat tolerant genotypes retained these attributes (Thorsted et al, 2006 ; Kiran and Chimmad, 2018 ). Similar results were reported in chickpea tolerant genotypes Raj-4037 and PBW590 under heat stress condition (Chaudhary et al, 2020 ). In other reports, it was observed that in maize, sorghum, and soybean under low soil moisture content diminishes, plant height, plant leaf and growth, dry matter, and eventually yield in susceptible genotypes (Ghosh et al, 2000 ; Khan et al, 2015 ).…”
Section: Discussionsupporting
confidence: 88%
“…It seems that heat‐tolerant wild genotypes that evolved in warmer regions have been able to develop heat‐adaptive strategies. Chaudhary et al (2020) noted that grain‐filling duration is a vulnerable stage to high temperature, which is directly associated with grain number and yield. In the present study, a positive association was observed between the length of the reproductive period, number and weight of grain, and grain yield in barley genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus as the grain (number and weight per spike) influences significantly from grain-filling duration and contributes significantly to final yield, reducing its number to enable heat tolerance or escape is likely to result in a substantial trade-off with yield. Chaudhary et al (2020) noted that grain-filling duration is a vulnerable stage to high-temperature which directly associated with grain number and yield. These findings are consistent with those reported by Bergkamp et al (2018) on wheat, indicating that terminal heat stress can shorten the grain-filling period via accelerated grain-filling rate, thereby causing a limited amount of carbohydrates transferred from the source tissues to the grains and reducing grain yield.…”
Section: Discussionmentioning
confidence: 99%